Accelerating Clean Energy Technology Research, Development, and Deployment : Lessons from Non-Energy Sectors - Avato, Patrick; Coony, Jonathan (Washington, DC : World Bank, 2012)
The World Bank Group's clean energy for development investment framework action plan has outlined some of the key activities it intends to undertake in the area of mitigating greenhouse gas emissions and helping client countries adapt to changes in climate. One of these activities focuses on an analysis of the role of low-carbon energy technologies in climate change mitigation. This report provides an initial analysis of this issue. The second chapter describes the urgency of developing new low-carbon energy technologies based on a review of some of the most authoritative recent reports on climate change. Strong evidence demonstrates the need for new and improved energy technologies, but, as is described in the third chapter, current research, development, and deployment (RD&D) efforts worldwide appear too limited and slow-paced to generate new energy technologies rapidly enough to respond to the climate change crisis. Moreover, significant barriers are limiting incentives to invest in energy RD&D and may reduce the effectiveness of such investments. These barriers are discussed in the fourth chapter. In light of these barriers and the very limited success of past attempts to overcome them, fifth chapter then analyzes four case studies where related barriers have been successfully overcome and public goods have been generated in non-energy sectors. These case studies are purposefully drawn from non-energy sectors to introduce new thinking to the energy sector and develop lessons learned to inform the development of novel and creative energy innovation vehicles. The sixth chapter draws lessons from these case studies that speak to creative ways to approach RD&D. The seventh and the final chapter summarizes findings and makes suggestion for follow-on work.